Analysis of Teacher Readiness Based on UTAUT2 in Utilizing Interactive Multimedia at State Madrasah Tsanawiyah in Bekasi Regency - Bayu Fadillah Akbar; Fatma Sukmawati; Salsabilla Suci Attalia (Universitas Sebelas Maret, 2026)
This study analyzes teachers' readiness to utilize interactive multimedia in learning at State Islamic Junior Secondary Schools (MTsN) in Bekasi Regency using the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) framework. The research employed a quantitative descriptive approach with 63 teachers as respondents selected through total sampling technique. Data were collected using a Likert scale questionnaire instrument comprising nine UTAUT2 constructs: performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, habit, behavioral intention, and use behavior. Results indicate that overall teacher readiness is at a high level with a mean score of 4.06. Performance expectancy achieved the highest score (M=4.34), followed by behavioral intention (M=4.27), hedonic motivation (M=4.07), effort expectancy (M=4.03), use behavior (M=3.98), and social influence and facilitating conditions (M=3.88 each). These findings demonstrate that teachers at MTsN in Bekasi Regency possess sufficient cognitive, technical, social, environmental, and motivational readiness to adopt interactive multimedia. The study contributes empirical evidence for applying UTAUT2 in Islamic education contexts and provides a strategic foundation for the Ministry of Religious Affairs in designing targeted teacher competency development programs.